Estimation of Age-specific Reference Intervals for Skewed Data - Moussa, M. A. A. (Methods of Information in Medicine, 2002)
Objectives: To compare Cole’s LMS method with Wright and Royston’s Exponential-Normal (EN) method for estimating reference intervals and generating smooth centile curves for the body mass index (weight in kg/height in meters squared) measurements of children aged 6 to 13 years.Methods: In the LMS method, the parameters L (the power needed to normalize the data), M (median) and S (coefficient of variation) are modeled as smoothed fits of maximum likelihood estimates. In the Exponential-Normal method, the three parameters mean, standard deviation and skewness are estimated separately using multiple regression techniques.Results: The centiles generated by the LMS and EN methods are close in most of the age groups. The 2.5th and 97.5th quantiles of the interval of the differences between the loss function scores of the LMS and EN methods calculated by bootstrap was found to include zero, indicating that the difference in loss function scores of the two methods is random and not systematic.Conclusions: The two methods are simple to use and generate comparable centile curves.
Keywords: Normal distribution; body mass index; regression; growth